2019
DOI: 10.5114/ceh.2019.87642
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic expression of programmed death-1 (PD-1) and its ligand, PD-L1, in children with autoimmune hepatitis: relation to treatment response

Abstract: Aim of the studyAutoimmune hepatitis (AIH) is characterized histologically by aggressive inflammation with interface hepatitis and prominent lymphoplasmacytic infiltration. Programmed death-1 (PD-1) is expressed on activated lymphocytes. Engagement of PD-1 by its ligand PD-L1 leads to cell apoptosis and death. We aimed to evaluate the immunohistochemical expression of PD-1 and PD-L1 in children with AIH, and its relation to treatment outcome.Material and methodsPre-treatment liver biopsies of 31 children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
3
9
0
Order By: Relevance
“…Importantly, the accumulation of PD-1 + CD8 + T cells in the untreated derived liver tissue correlated positively with liver pathology (ALT and A possible involvement of PD-1/PD-L1 pathway in the pathogenesis of AIH w described in mice model of experimental AIH [20] and in human studies [ sults are in accordance with Oikawa et al, who previously demonstrated histochemistry that PD-1 ICM is expressed on more than half of the intrahe patients with AILD [21]. Similarly, a recent study showed a high frequency tive cells within liver tissue in children with AIH [22]. However, neither o determined the exact type of intrahepatic T cells that express the PD-1 mole ing levels of PD-1 are also increased in AILD, as recent studies have shown t levels of soluble PD-1 are elevated in AIH patients [23,24].…”
Section: Discussionsupporting
confidence: 74%
“…Importantly, the accumulation of PD-1 + CD8 + T cells in the untreated derived liver tissue correlated positively with liver pathology (ALT and A possible involvement of PD-1/PD-L1 pathway in the pathogenesis of AIH w described in mice model of experimental AIH [20] and in human studies [ sults are in accordance with Oikawa et al, who previously demonstrated histochemistry that PD-1 ICM is expressed on more than half of the intrahe patients with AILD [21]. Similarly, a recent study showed a high frequency tive cells within liver tissue in children with AIH [22]. However, neither o determined the exact type of intrahepatic T cells that express the PD-1 mole ing levels of PD-1 are also increased in AILD, as recent studies have shown t levels of soluble PD-1 are elevated in AIH patients [23,24].…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, imbalanced expression of PD-1/PD-L1 has previously been reported in inflamed livers of PBC and AIH patients 41,42 . Moreover, recent case reports on the development of secondary sclerosing cholangitis in patients receiving checkpoint inhibitor treatment highlight the functional importance the PD-L1/PD-1 axis for biliary immune homeostasis 43,44 .…”
Section: Mechanistically Cd8 + T Cell-derived Il-17 Induced the Exprmentioning
confidence: 81%
“…Binding of PD-L1 to PD-1 leads to T cell dysfunction by inhibiting T cell activation, causing T cell exhaustion, anergy, and T cell apoptosis, as well as by inducing Treg differentiation [7][8][9][10][11]. In addition, elevated PD-L1 levels in liver were observed in chronic necroinflammatory liver diseases and autoimmune hepatitis [12,13]. These indicate the immune regulatory function of the liver microenvironment that may lead to T cell exhaustion.…”
Section: Introductionmentioning
confidence: 99%